Expression Of Androgen Receptor, Estrogen Receptor And Progesterone Receptor In Endometrial Carcinoma (Immunohistochemical Study) - Mangal, Suruchi; Sharma, Manisha; Manjari, Mridu; Mannan, Rahul; Tandon, Sunit (Annals of Pathology and Laboratory Medicine, 2020)
BACKGROUND Endometrial carcinoma is the most common pelvic genital malignancy and 4th most frequently diagnosed cancer in females with it’s incidence being 4.3/ 1 lac females. METHODS: Thirty histologically proven cases of endometrial carcinoma were taken up for the study in pathology department. Immunohistochemistry for expression of androgen receptor (AR), estrogen receptor (ER) and progesterone receptor (PR) was done using Biocare system kit. RESULTS: 80% of the cases were in 5th and 6th decade of life. Bleeding per vagina and post menopausal bleeding were the main complaints. Out of the total 22 abdominal hysterectomies the size of tumor varied from 1cm to >4cm. All were adenocarcinoma with 20 being moderately differentiated and only 2 being well differentiated. AR was positive in 8 cases with ER and PR being positive in 16 and 21 cases respectively with score being also the same. Receptor positivity decreased with increasing grade of the tumor. CONCLUSION: ER and PR status are important prognostic biomarkers which also predict response to antihormonal therapy in endometrial carcinoma. AR expression though associated with low grade tumors , but still is a driver for tumor growth and therefore a potential therapeautic target. Anti androgen therapy - enzalutamide may inhibit proliferation of AR positive primary endometrial cancer cells.